Economic Empowerment Strategy of Pesantren in Salafiyah Syafi'iyah Sukorejo Islamic Boarding School Owned Enterprises Situbondo Regency - Latifah, Sofiyatul; Nafis, Abdul Wadud; Qoriani, Hersa Farida (Ridwan Institute, 2024)
Pesantren that live in the midst of society certainly have a great influence on people's lives. In Law no. 18 of 2019 concerning pesantren that there are three roles of pesantren in the implementation of educational functions, da'wah functions and community empowerment functions. Pesantren with its business entities certainly provide great opportunities and become a forum for community empowerment. The success of this empowerment affects the improvement of people's living standards and can even realize welfare through the roles of pesantren. However, there are several problems experienced such as low human resources, low income, there are some pesantren businesses that are not developing. Therefore, it is necessary to design a strategy to compile a business design systematically balanced with mentoring, training and evaluation. This research uses a qualitative approach with a phenomenological type of research location in a business entity owned by the Salafiyah Syafi'iyah Sukorejo Islamic boarding school, Banyuputih District, Situbondo Regency. Data collection is done through interviews, conservation and documentation. The results of this study show that the strategy of economic empowerment of pesantren in pesantren-owned enterprises is carried out with three strategies including: strategy formulation, strategy implementation, and strategy evaluation. Strategy formulation includes: first, formulation of policy direction for economic development of pesantren.